Faktor–Faktor Yang Berpengaruh Terhadap Kejadian Asma Bronkial Pada Anak di Puskesmas Saitnihuta Kabupaten Humbanghasundutan - Winta Winta; Fransiska Fransiska; Nova Nova (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
The prevalence of asthma in Indonesia above <1 year 1.1%, Asthma causes a loss of 16% of school days in children. To determine the factors that affect the incidence of bronchial asthma in children. Asthma is a condition in which the airway is narrowed due to hyperactivity to certain stimuli that cause inflammation. The research method used case control study method. The diagnosis of asthma is based on anamnesis, clinical signs, additional examination. The control group were children who were not found to have asthma based on anamnesis, clinical signs, additional examination by pediatricians. The data were analyzed by univariate, bivariate, and chi square test. The result of research of risk factors influencing the incidence of asthma are sex (OR = 8,25, 95% CI, 1,252-54,364; p = 0,028), pet ownership (OR = 30,65; 95% CI; 1,538-610; (OR = 19.27; 95% CI: 2,169-171,3; p = 0.008), family illness history (OR = 8,27; 95% CI; 1,505-45,434; p = 0.015), cigarette smoke (OR = 23,13; 95% CI; 4,141-129,2; p = <0.001). The probability of individuals for bronchial asthma with all risk factors was 46.51%. Risk factors that affect the incidence of bronchial asthma are gender, pet ownership, climate change, family history, cigarette smoke. Suggestion for the public to be vigilant if any occurrence of shortness of breath to immediately contact health officer for further management.